A scoping review of the individual, socio-cultural, environmental and commercial determinants of gambling for older adults: implications for public health research and harm prevention - Rebecca H. Johnson; Hannah Pitt; Melanie Randle; Samantha L. Thomas (BMC, 2023)
Abstract Gambling is a global public health issue that can cause harm to individuals, families, and communities. Older adults are vulnerable to gambling harm due to life-stage experiences. This study aimed to examine current research relating to individual, socio-cultural, environmental, and commercial determinants of gambling among older adults. A scoping review was conducted (PubMed, PsycInfo, SocIndex, CINAHL Complete, Web of Science, Social Science and Sociology databases available in ProQuest, Google Scholar, citation searching), with peer reviewed studies included that were published between 1 December 1999 and 28 September 2022. Included studies were published in English in peer-reviewed journals that examined the determinants of gambling in adults aged 55 and over. Records were excluded if they were experimental studies, prevalence studies or had a population wider than the required age group. Methodological quality was assessed using JBI critical appraisal tools. Data was extracted using a determinants of health framework and common themes were identified. Forty-four were included. Most literature examined individual and socio-cultural determinants including reasons for gambling, risk management strategies, and social motivations for gambling. Few studies investigated environmental or commercial determinants, and those that did focused on accessibility of venues or promotions as pathways to gambling. Further research is needed to understand the impact of gambling environments and industry, and effective public health responses for older adults.